How effectively can nurture groups be used in improving outcomes for young children with emotional, behavioural and social difficulties in primary schools? - Sun, Jiwei; Du, Hong (Technium Social Sciences Journal, 2023)
Emotional, social, behavioral, and mental health disorders in young children are increasingly prevalent and may have long-term effects, persisting from preschool into primary school (Carroll & Hurry, 2018). Such challenges can significantly impact children’s ability to adapt to the classroom and access learning opportunities. To address these challenges, Boxall (2002) developed the concept of nurture groups, where a small group of students is removed from their regular classes for a limited period during the school year to model positive attachment relationships, develop emotional literacy, and provide opportunities for social learning while maintaining access to education (Loinaz, 2015). This literature review aims to explore the effectiveness of nurture groups in improving outcomes for young children with emotional, behavioral, and social difficulties in primary schools. The study reviews existing literature, examining the positive effects of nurture groups on children’s well-being, while also critiquing current research. The results suggest that children with a broad spectrum of social, emotional, and behavioral difficulties may benefit from nurture groups, thereby making a strong case for creating nurturing schools. However, one potential concern is that some students who thrive in nurturing schools may struggle when they return to mainstream classes. Therefore, further comparable studies on a larger scale are required.